Comparative analysis of MPPT techniques for enhancing a wind energy conversion system - Gaied, Hajer; Naoui, Mohamed; Kraiem, Habib; Goud, B. Srikanth; Flah, Aymen; Alghaythi, Mamdouh L.; Kotb, Hossam; Ali, Samia G.; Aboras, Kareem (Frontiers in Energy Research, 2022)
One of the most reliable and advanced renewable energy sources is wind energy. It's critical to harness as much wind 20 energy as possible and maintain wind turbines operating at full capacity. Maximum power point tracking (MPPT) is a cutting-edge 21 study that incorporates a variety of approaches. Because each MPPT technique has its own set of advantages and disadvantages, 22 developing an accurate maximum power point tracking methodology for a certain case necessitates understanding. As a result, 23 they must be checked thoroughly. This research tries to examine many algorithms that can be used to improve the wind energy 24 system's global MPPT performance, 25 26 27 The advantages, drawbacks, and thorough analysis of MPPT systems are highlighted in terms of initial investment, 28 All of this comparison was made through simulation software, 29 which is the MATLAB Simulink tool. The conclusions are supported by a comprehensive discussion and presentation of the re- 30 sults for a variety of situations and tests that reflect real-world behavior in any wind system.